A theoretical investigation of the two-photon absorption and fluorescent properties of coumarin-based derivatives for Pd2+ detection. Issue 78 (24th October 2017) - Zhang, Chun; Guo, Jing-Fu; Ren, Ai-Min; Wang, Dan
Abstract : Two-photon fluorescent probes that can detect Pd 2+ according to the "turn-on" fluorescence signal are reported. Abstract : Palladium is emitted due to automobile catalytic converters, and with rapid growth in the number of cars, palladium is thus a current threat to human health and the environment. Two-photon (TP) fluorescent probes are favorable and powerful molecular tools for palladium ion (Pd 2+ ) detection due to localized excitation and reduced phototoxicity and photodamage. In the present study, a series of "turn-on" TP fluorescent dyes based on coumarin derivatives were designed for Pd 2+ recognition. Our study revealed the origin of the peculiarly different fluorescence behaviors of the synthesized Pd 2+ probe R1 and the product P′1 quantitatively and qualitatively from a theoretical perspective. Moreover, quantum-chemical calculations on electronic structures, one/two-photon absorption and fluorescence optical properties have first been carried out for these TP fluorescent chromophores using an ab initio approach. The calculated results demonstrate that chemical modifications of the coumarin core by the introduction of an electron-withdrawing group (–Cl or –CN) to its 4-position effectively increase the TP absorption cross-section per molecular weight more easily than extending the π-conjugated structure at the 3-position. In the present work, the product P′4, with a much smaller internal conversion rate ( K IC = 1.28 × 10 6 s −1 ) than that of the Pd 2+ probe R4 ( K IC = 9.09 × 10 11 s −1 ), possesses the largest TP absorption cross-section per molecular weight (3.91) and the longest fluorescence wavelength (590.3 nm) among all the studied molecules, which means it has better potential for Pd 2+ detection. Consequently, we hope that this detailed study can provide guidance for the design and synthesis of new Pd 2+ fluorescent probes.